Clinical characteristics and antibody response to SARS-CoV-2 spike 1 protein using VITROS Anti-SARS-CoV-2 antibody tests in COVID-19 patients in Japan. Issue 4 (16th April 2021) - Nagura-Ikeda, Mayu; Imai, Kazuo; Kubota, Katsumi; Noguchi, Sakiko; Kitagawa, Yutaro; Matsuoka, Masaru; Tabata, Sakiko; Miyoshi, Kazuyasu; Ito, Toshimitsu; Tamura, Kaku; Maeda, Takuya
Abstract : Introduction. Serological tests for COVID-19 are important in providing results for surveillance and supporting diagnosis. Investigating the serological response in COVID-19 patients with different disease severity is important for assessing the clinical utility of serological assays. Gap Statement. However, few studies have investigated the clinical utility of antibody assays for COVID-19 or differences in antibody response in association with disease severity. Aim. The study aimed to evaluate the clinical characteristics and clinical utility of VITROS SARS-CoV-2 antibody tests according to COVID-19 severity in patients in Japan. Methodology. We analysed 255 serum specimens from 130 COVID-19 patients and examined clinical records and laboratory data. Presence of total (IgA, IgM, and IgG) and specific IgG antibody for the spike 1 antigen of SARS-CoV-2 was determined using VITROS Anti-SARS-CoV-2 antibody tests. Results. Overall, 98 (75.4 %) and 32 (24.6 %) patients had mild and severe COVID-19, respectively. On admission, 76 (58.5 %) and 45 (34.6 %) patients were positive for total and IgG antibody assays. Among 91 patients at discharge, 90 (98.9 %) and 81 (89.0 %) were positive for total and IgG antibody, respectively. Clinical background and laboratory findings on admission, but not the prevalence or concentration of total or IgG antibody, were associated with disease prognosis. Total and IgG antibody intensities were significantly higher in severe cases than in mild cases in serum collected >11 days after onset, but not within 10 days. Conclusion. VITROS Anti-SARS-CoV-2 total and IgG assays will be useful as supporting diagnostic and surveillance tools and for evaluation of humoral immune response to COVID-19. Optimal prediction of disease prognosis is made from considering both clinical history and laboratory findings.